Roosevelt High and Fresno High Pig Bowl Football Game at McClane Stadium - Watkins, Howard::::::::: (1983)
Roosevelt High quarterback #88 calling play; #60 is Chris Petersen Other Roosevelt player numbers: 70 and 5